Synthesis and Bio‐evaluation of GR135486X Derivatives as Potent Anti‐Tubercular Agents. Issue 1 (2nd January 2023) - Sangu, Komal G.; Dasugari varakala, Saiprasad; Krishna, Eruva Vamshi; Akhir, Abdul; Saxena, Deepanshi; Ahmad, Mohammad Naiyaz; Chopra, Sidharth; Misra, Sunil; Sriram, Dharmarajan; Rode, Haridas B.
Abstract: The anilinopyridine derivatives were designed, synthesized and evaluated against Mycobacterium tuberculosis H37Rv. The detail SAR study was carried out using various analogues including positional isomers. The screening data revealed that the free −NH2 on pyridine ring is crucial for antitubercular activity. The current study identified three promising leads 16 e, 16 i and 16 o with MIC 3.1, 3.1 and 1.2 μM, respectively. Important to note that the compound 16 o showed excellent selectivity index of 135.58 when its antitubercular activity was compared with the inhibition of CHO−K1 cells. The other notable compounds were 16 b, 16 d, 16 e, 16 f, 16 g, 16 h, 16 i, 16 l and 16 q which exhibited anti‐TB activity with MIC ≤25 μM. Interestingly, compounds 16 e, 16 i and 16 o did not show inhibition of bacterial pathogen panel indicating the selectivity of this class of compounds towards Mtb. Furthermore, physico‐chemical and ADMET properties of the synthesized derivatives were studied. The compounds fulfill the criteria of Lipinski's rule of five for drug‐likeness. Abstract : Anilinopyridine derivatives were synthesized and evaluated against Mycobacterium tuberculosis H37Rv. Compound 16 o showed MIC of 1.2 μM against Mycobacterium tuberculosis H37Rv and excellent selectivity index of 135. The structural modification indicates requirement of free NH2 group on the pyridine ring for antitubercular activity. Compound 16 o is a selective inhibitor of Mycobacterium tuberculosis H37Rv as it has not shown inhibition of ESKAPE pathogen.